2010
DOI: 10.1007/s00296-010-1468-4
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of semi-automated measurements of finger joint space widths

Abstract: The purpose of this study is to evaluate technical feasibility based on image capturing conditions (film-focus distance (FFD), film sensitivity, film brand, exposure level and tube voltage) that potentially alter radiographs and consequently may influence the semi-automated measurement of joint space distance (JSD) by computer-aided joint space analysis (CAJSA) in rheumatoid arthritis and osteoarthritis. The radiographs of a left hand (deceased man) were acquired under systematically changing image capturing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…A previous study showed that technical parameters, such as exposure level, film brand, film sensitivity, and film focus distance, do not affect the reproducibility of CAJSA measurements during the image-acquisition process [13]. Recently published data presented no influence of hand rotation on CAJSA measurements with the exception of a hand rotation of more than 15° during X-ray imaging, which is complementary to an oblique acquired hand radiograph and should be not used for CAJSA measurements [11].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that technical parameters, such as exposure level, film brand, film sensitivity, and film focus distance, do not affect the reproducibility of CAJSA measurements during the image-acquisition process [13]. Recently published data presented no influence of hand rotation on CAJSA measurements with the exception of a hand rotation of more than 15° during X-ray imaging, which is complementary to an oblique acquired hand radiograph and should be not used for CAJSA measurements [11].…”
Section: Discussionmentioning
confidence: 99%
“…As a potential limitation of our study, the influence of X-ray imaging parameters as well as joint gap width detection should be discussed. In this context, an experimental study revealed no significant influence of the image acquisition protocol on measurement JSD [29]. Additionally, the CAJSA-system checked the image quality and stopped the measurements if the image quality was poor and if there was a misalignment of the joints.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, many of the presented methods have been tested on datasets from one institute, in which hand radiographs were acquired via the same radiographic protocol [7,28]. Pfeil et al reported that computer-aided analysis for joint space measurements is affected by alternation of tube voltage to a lesser extent [29]. Therefore, we used datasets from two institutions with different digital image acquisition systems to demonstrate that our computer-based method can allow shared use by several users in different locations.…”
Section: Discussionmentioning
confidence: 99%